Peranan Decision Support System (DSS) bagi Manajemen Selaku Decision Maker - Aprilia Whetyningtyas (Jurnal Analisis Manajemen, 2011)
The rapidly technology process on globalisasion era in business world, makes the decision making is the important thing to make decision faced with the competition in business world. The decision making can be influence by a few aspect, which can influence the decision maker to accelerate perfectly and correctly the decision making. The development of information system and information technology was to give birth to a decision support system or DSS. DSS is a computer based system, almost always interactive, designed to assist a manager (or another decision maker) in making decision. The purpose of this paper is to assess the benefit of DSS to management as decision maker. More specifically, this paper provides a summary of DSS can result a correct and flexible decision with aspect which influence that decision, and give a report in order to user can understand why this software choose that decision.